Perspective on quantum bubbles in microgravity. (1st April 2023) - Lundblad, Nathan; Aveline, David C; Balaž, Antun; Bentine, Elliot; Bigelow, Nicholas P; Boegel, Patrick; Efremov, Maxim A; Gaaloul, Naceur; Meister, Matthias; Olshanii, Maxim; Sá de Melo, Carlos A R; Tononi, Andrea; et al.
Abstract: Progress in understanding quantum systems has been driven by the exploration of the geometry, topology, and dimensionality of ultracold atomic systems. The NASA Cold Atom Laboratory (CAL) aboard the International Space Station has enabled the study of ultracold atomic bubbles, a terrestrially-inaccessible topology. Proof-of-principle bubble experiments have been performed on CAL with an radiofrequency-dressing technique; an alternate technique (dual-species interaction-driven bubbles) has also been proposed. Both techniques can drive discovery in the next decade of fundamental physics research in microgravity.